2014
DOI: 10.1179/1743284713y.0000000428
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured steel industrialisation: Plausible reality

Abstract: It is not the first time that a consortium of steel makers, end users and scientists ends up with unique approaches and developments in the physical metallurgy of steels. This paper reveals the scientific and technological developments of a consortium sharing a common intrigue and interest for a unique microstructure, nanostructured bainite. Also known as low temperature bainite, as its unique properties rely solely on the scale of the miscrostructure obtained by heat treatment at low temperature (150-350ºC). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
53
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 33 publications
(82 reference statements)
3
53
0
3
Order By: Relevance
“…A recent work [9,42] on a large set of nanobainitic structures from different steels and heat treatments clearly revealed that there is no overall correlation between the initial austenite content and either the uniform elongation or the total elongation, Figure 8. A recent work [9,42] on a large set of nanobainitic structures from different steels and heat treatments clearly revealed that there is no overall correlation between the initial austenite content and either the uniform elongation or the total elongation, Figure 8.…”
Section: Ductility and Retained Austenite Contentmentioning
confidence: 98%
See 2 more Smart Citations
“…A recent work [9,42] on a large set of nanobainitic structures from different steels and heat treatments clearly revealed that there is no overall correlation between the initial austenite content and either the uniform elongation or the total elongation, Figure 8. A recent work [9,42] on a large set of nanobainitic structures from different steels and heat treatments clearly revealed that there is no overall correlation between the initial austenite content and either the uniform elongation or the total elongation, Figure 8.…”
Section: Ductility and Retained Austenite Contentmentioning
confidence: 98%
“…A recent work [9,42] on a large set of nanobainitic structures from different steels and heat treatments clearly revealed that there is no overall correlation between the initial austenite content and either the uniform elongation or the total elongation, Figure 8.…”
Section: Ductility and Retained Austenite Contentmentioning
confidence: 98%
See 1 more Smart Citation
“…First, as the same theory used for the design of such alloys predicts, the transformation slows down dramatically as the transformation temperature is reduced, and it may take as long as 10 to 20 h to fully transform to bainite [4,5]. Second, due to their high carbon content, the steels are difficult to weld because of the formation of untempered, brittle martensite in the coarse grained heat affected zones of the joints.…”
Section: Nanostructured Bainitementioning
confidence: 99%
“…%) high silicon (1.5-3 wt. %) steels were designed to produce incredibly fine plates of bainitic ferrite, 20-40 nm thick, separated by a percolating network of retained austenite after transformation at 200-350 • C [4,5]. The scale of this structure is such that it contains a remarkably large density of interfaces, making it very strong even without the presence of a substantial fraction of carbide precipitates.…”
Section: Nanostructured Bainitementioning
confidence: 99%